Peningkatan Penalaran Dan Hasil Belajar MenggunakanMedia Macromedia Flash Pada Siswa Kelas ViiidSMP Negeri 1 Geyer Tahun Ajaran 2015/2016 - Oktaviani, Riris (2016)
This study aimstodetermine the increaseof mathematicalreasoning andlearning outcomes of studentswith Macromedia Flashmedia. The subject ofthe action recipient sarestudents of class VIII D SMPN 1 Geyernumbered 28students, teachersactas subjectsgiveraction, the researcheras an observer. The research methodis done bycollecting data through observation, interviews, tests, field notes, anddocumentation. Data analysis techniques inthe studycarried outbythe flowmethod, including data reduction, data presentation, and conclusion. Research datashows the increaseof mathematical reasoning andlearning outcomes. Increase dreasoning and student learning outcomescan be seenfrom1) shows thedata manipulationbeforeactionof13 students(46.43%) in the first cycleto 19students (67.58%) increasedthe second cycleto 25students (89.286%), 2) the ability to explainideasand statements ofmathematics beforeactionof 10 students(35.714%) inthe first cycle to12 students (42.875%) andincreasethe second cycleto 23students (82.143%), 3) the abilityto draw conclusions before the actionof 6 students(21.429%) the first cycle to10students (35.714%) and increase the second cycleto 25students (89.286%), 4) the ability of studentstowork onself-test completed KKM befor eaction of 12 students(42.857%), the first cycle to19 students (67.857%) and increas ethe second cycleto 28 students (100%) afterthe action. The conclusion of this studyis toimprove themedia Macro media Flas hre asoning and mathematics learning ou tcomes